(untitled) (Jurnal De Jure Muhammadiyah Cirebon, 2025)
The process of warehouse rental agreement between the lessee and the PT. (Persero) Bhanda Ghara Reksa Warehouse, once there is an agreement regarding the provision of a warehouse, the rental period and the warehouse rental fee, then usually the goods belonging to the prospective lessee can be sent immediately even though the rental agreement has not been made. So even though the warehouse rental agreement has not been made, the prospective lessee can put their goods in the warehouse and the warehouse is willing to accePT them, this is done to facilitate the smooth running of business for both parties. Rights of the warehouse and the lessee: The right of the warehouse is to receive rent and money from loading and unloading costs and other costs/fees related to the lessee’s goods; The right of the lessee is to be able to enjoy the use of the warehouse for storing their goods peacefully and free from third party interference. The obligation of the warehouse is to hand over the right to use the warehouse to the lessee; The lessee is obliged to maintain the warehouse and all provisions or provision of facilities and facilities belonging to the warehouse that he rents as well as possible; The lessee is obliged to pay the warehouse rental price and other costs related to the warehouse rental at the time specified in the warehouse rental agreement. Keywords: Agreement, Rental, Warehouse